Pengaruh Tingkat Pemahaman Akuntansi, Fungsi Badan Pengawas Dan Profesionalisme Terhadap Kualitas Laporan Keuangan Lembaga Perkreditan Desa (LPD) Di Kecamatan Abiansemal Kabupaten Badung - Putu Elfreda Carissa Aspasia; Dr. Cokorda Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2023)
Each LPD certainly provides financial reporting that can provide the information users need. This study was conducted to determine the effect of the level of understanding of accounting, the function of the supervisory body and professionalism on the quality of financial reports in LPDs in Abiansemal sub-district. The population used in this study were 33 LPDs in Abiansemal District. The number of samples in this study was 199. The analytical technique used was multiple linear regression analysis. Based on the results of the analysis, it is known that the level of understanding of accounting, the function of the supervisory body and professionalism has a positive effect on the quality of financial reports at the Village Credit Institution or LPD in Abiansemal District.